Phthalocyanine-Aggregated Polymeric Nanoparticles as Tumor-Homing Near-Infrared Absorbers for Photothermal Therapy of Cancer - Lim, Chang-Keun; Shin, Jiyoung; Lee, Yong-Deok; Kim, Jungahn; Oh, Keun Sang; Yuk, Soon Hong; Jeong, Seo Young; Kwon, Ick Chan; Kim, Sehoon (IVYSPRING INT PUBL, 2012)
Phthalocyanine-aggregated Pluronic nanoparticles were constructed as a novel type of near-infrared (NIR) absorber for photothermal therapy. Tiny nanoparticles (similar to 60 nm, FPc NPs) were prepared by aqueous dispersion of phthalocyanine-aggregated self-assembled nanodomains that were phase-separated from the melt mixture with Pluronic. Under NIR laser irradiation, FPc NPs manifested robust heat generation capability, superior to an individual cyanine dye and cyanine-aggregated nanoparticles. Micro-and macroscopic imaging experiments showed that FPc NPs are capable of internalization into live cancer cells as well as tumor accumulation when intravenously administered into living mice. It is shown here that continuous NIR irradiation of the tumor-targeted FPc NPs can cause phototherapeutic effects in vitro and in vivo through excessive local heating, demonstrating potential of phthalocyanine-aggregated nanoparticles as an all-organic NIR nanoabsorber for hyperthermia.
Keywords: 808-NM DIODE-LASER; CARBON NANOTUBES; CELL DESTRUCTION; DISC; DYE; POLYCARBONATE; ABLATION; AGENTS; STATE